Mechanism by Which Backfill Body Reduces Amount of Energy Released in Deep Coal Mining - Wenyue Qi; Jixiong Zhang; Nan Zhou; Zhongya Wu; Jun Zhang (Shock and Vibration)
Deep coal mining is unavoidable, and the complex mining environments and the increasing dangers associated with ultrahigh energy accumulation and release from mining disturbances renders it extremely difficult to maintain a safe and stable stope. Solid backfilling technology directly uses coal gangue and other solid wastes in the mining area to fill the gob after mining. Support from the backfill body can inhibit the movement of overlying rock strata and significantly alleviate the influence of mining. In this study, the correlations between the deformation of gangue filling material and the characteristics of energy dissipation were examined under lateral uniaxial compression. The strain energy density distributions of backfilling and caving mining methods were simulated using numerical modeling. The results showed that the strain energy density distribution of backfilling mining was less concentrated, and its peak value was lower than that of caving mining by 51.0%, indicating that backfilling could effectively reduce the amount of energy released from mining rocks. The dense backfill mining area of the No. 9301 face in Tangkou Coal Mine was used as a case study. Measures for controlling the backfill body compaction for reducing the amount of energy released from mining rocks were proposed. These measures include optimizing the support structure and filling material formula, controlling the preroof subsidence, and ensuring an appropriate number of tamping strokes. The monitoring results of the backfilling quality, surface subsidence, and microseismic energy of No. 9301 working face in Tangkou Coal Mine showed that when the backfill body filling ratio control value was 82.28%, the total number of microseisms and the amount of energy released from the mining working face were significantly lower compared to those of the caving method. This study demonstrated that the backfill body could effectively reduce the amount of energy released from mining rocks, thereby realizing management of mine earthquake and sustainable deep coal mining.